2015
DOI: 10.1021/jp511929v
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electronics as a Function of Size and Surface of Colloidal Germanium Nanocrystals

Abstract: Inorganic semiconductor nanoparticles are of significant interest for applications that benefit from their size-dependent properties. The work presented here focuses on the characterization of solution-based microwave synthesized Ge nanocrystals (NCs).Three differently capped Ge NCs were investigated: oleylamine (OAM), dodecanethiol (DDT), and a functionalized N4,N4,N4',N4'-tetraphenylbiphenyl-4,4'-diamine (TPD) ligand, which is commonly used as hole-transporting units. The optical gaps followed the expected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…Ligand‐induced changes in the optical properties of Ge NCs have been reported by Holmes et al, who showed a consistent 0.15 eV difference in the optical band gap of oleylamine and dodecanethiol capped NCs across a range of NC diameters (4.0, 5.4, and 7.6 nm) . They attributed these effects to changes in the atomic arrangements at the NC surface caused by different binding groups, which in turn modifies the band gap of the material.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Ligand‐induced changes in the optical properties of Ge NCs have been reported by Holmes et al, who showed a consistent 0.15 eV difference in the optical band gap of oleylamine and dodecanethiol capped NCs across a range of NC diameters (4.0, 5.4, and 7.6 nm) . They attributed these effects to changes in the atomic arrangements at the NC surface caused by different binding groups, which in turn modifies the band gap of the material.…”
supporting
confidence: 54%
“…Numerous approaches to combine synthesis and passivation of the Ge NC surface have been reported in the literature, including one‐pot methods, controlled synthesis, microwave heating, and even alloyed/doped Ge NCs . Several groups have reported the use of oleylamine as a capping ligand, while alkyl compounds, phosphines, and other functional groups have also been used .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] As another type of important elemental semiconductor NCs, Ge NCs hold a unique position because of a series of advantageous materials properties, including strong optical absorption and high mobilities of electronic carriers. [ 29 ] Although Ge NCs can now be controllably synthesized, [30][31][32] the doping of Ge NCs has been rarely explored. The delayed development of Ge NCs in doping may seriously limit the realization of the full potential of Ge NCs in a variety of applications.…”
mentioning
confidence: 99%
“…where the precursor ratio controls the particle size. 46,[69][70][71][72][73] The polymerization of [Ge9] 4or other related Zintl ions, both with and without linking cations such as Ge 4+ or Pt 2+ , generates highly ordered, porous Ge nanocrystals. [74][75][76][77][78] Other preparations involve reduction of Ge-rich oxides, [79][80][81][82][83][84] heat-assisted reduction of the GeH2 Wittig adduct Ph3PCMe2·GeH2·BH3, [85][86] laser photolysis of Ge(CH3)4 or GeH4 gas, 87-89 photolysis of Ge wafer, 90 electroless deposition on preformed Ag nanocrystals, 91 Au-catalyzed vaporliquid-solid growth using GeH4 92 or diphenylgermane, 93 ultrasonic aerosol pyrolysis of tetrapropylgermane, 94 solution or solid phase reduction of NaGe, 95 plasma decomposition of GeCl4 [96][97][98] or GeH4, 99 sulfur-assisted thermal decomposition of triphenylgermanium chloride, 100 and heating a solution of an alkylgermane in various high-temperature organic solvents.…”
Section: Introductionmentioning
confidence: 99%